Modulation of Bladder Wall Micromotions Alters Intravesical Pressure Activity in the Isolated Bladder - Chakrabarty, Basu; Bijos, Dominika A.; Vahabi, Bahareh; Clavica, Francesco; Kanai, Anthony J.; Pickering, Anthony E.; Fry, Christopher H.; Drake, Marcus J. (Frontiers in Physiology, 2019)
Micromotions are phasic contractions of the bladder wall. During urine storage, such phasic activity has little effect on intravesical pressure, however changed motile activity may underlie urodynamic observations such as detrusor overactivity. The potential for bladder motility to affect pressure reflects a summation of the overall movements, comprising the initiation, propagation, and dissipation components of micromotions. In this study, the influence of initiation of micromotions was investigated using calcium activated chloride channel blocker niflumic acid, and the effect of propagation using blockers of gap junctions. The overall bladder tone was modulated using isoprenaline. Isolated tissue strips and whole bladder preparations from juvenile rats were used. 18β-glycyrrhetinic acid was used to block gap junctions, reducing the amplitude and frequency of micromotions in in vitro and ex vivo preparations. Niflumic acid reduced the frequency of micromotions but had no effect on the amplitude of pressure fluctuations. Isoprenaline resulted in a reduction in pressure fluctuations and a decrease in pressure baseline. Using visual video data analysis, bladder movement was visible, irrespective of lack of pressure changes, which persisted during bladder relaxation. However, micromotions propagated over shorter distances and the overall bladder tone was reduced. All these results suggest that phasic activity of the bladder can be characterised by a combination of initiation and propagation of movement, and overall bladder tone. At any given moment, intravesical pressure recordings are an integration of these parameters. This synthesis gives insight into the limitations of clinical urodynamics, where intravesical pressure is the key indicator of detrusor activity.